Characterization and evaluation of commercial fragrance microcapsules for textile application - Rodrigues, C.S.N. (2012)
In this paper, some commercial microcapsule samples, containing different fragrances used for textile application purposes, were characterized and evaluated. Microcapsule samples were evaluated in terms of particle size, morphology, shell material composition, and fragrance intensity. The effectiveness of the textile impregnation and its durability were assessed. The selection of samples used in each study was made in order to the specific goals of characterization and evaluation of microcapsules. Lemon_Bayer, Lemon_Focor, Lemon_Horquim, Strawberry_Horquim, and Jasmine_Focor samples were used to study the morphology and particle size distribution, and it was observed that microcapsules have a spherical shape with size between 2 and 6 lm. The chemical composition of Lavender_Horquim, Mints_Horquim, Eucaliptus_Focor, and Apple_Focor samples was checked/ confirmed and was based on melamine copolymers including melamine-formaldehyde ones. Lemon_Horquim microcapsules were impregnated on textile substrates, and it was observed that a loss of 46% of limonene occurred after one domestic wash and a loss of 97% occurred after 20 domestic washes.